Simultaneous use of convection and radiation heat transfer for Iranian pistachio drying using catalytic heater - numerical and experimental study - Ebrahimpour, Vahid; Esmailpour, Kazem (Frontiers in Mechanical Engineering, 2024)
This study presents a comprehensive investigation into the simultaneous use of convection and radiation heat transfer for Iranian pistachio drying using a catalytic heater. Both experimental and numerical analyses were conducted to evaluate the performance of the proposed system. The experimental setup involved a catalytic infrared heater, which provided a consistent temperature of approximately 370 K within the drying chamber. The results indicated that the drying time was reduced by 40% compared to traditional hot air drying methods, with an average moisture reduction rate of 0.8% per minute. The numerical analysis, conducted using computational fluid dynamics (CFD) simulations, supported the experimental findings, showing a uniform temperature distribution across the pistachios and efficient heat transfer. The catalytic heater demonstrated a combustion efficiency of 98%, with CO emissions below 10 ppm and zero NOx emissions, highlighting its environmental benefits. Overall, the combined experimental and numerical results confirmed that the proposed catalytic heater system not only enhances drying efficiency but also significantly reduces energy consumption and greenhouse gas emissions compared to conventional drying methods.